M. Salomon Möllerus Gedan. Ad S. Joh. Pastor, Natus A. 1641. D. 9. Oct. Denatus A. 1687. D. 19. Junii. / E. Hainzelmann. - Hainzelmann, Elias (1640-1693) (1687)
Przedstawia portret w popiersiu Salomona Möllera (1641-1687), pastora kościoła św. Jana w Gdańsku.